Vaginal preparation with chlorhexidine before cesarean section and the rate of endometritis and post-operative wound infection - Khadijah Elmizadeh; Shokohossadat Haj Seyyed Abotorabi; Nasibeh Parsaei Athar; Simindokht Molaverdikhani (Mashhad University of Medical Sciences, 2024)
Introduction: Endometritis and wound infection after caesarean section is the most common complication of caesarean section and is associated with many problems and complications. The present study was conducted with aim to determining the effect of vaginal washing with chlorhexidine before cesarean section on endometritis and wound infection after cesarean section. Methods: This randomized clinical trial study with a control group was conducted in 2021-2022 on 320 patients with indications for cesarean section referred to the Kowsar Hospital in Qazvin, Iran. Before cesarean section, the patients were divided into two groups of test (vaginal prep with chlorhexidine) and control (vaginal prep with normal saline serum). During the first 10 days after cesarean section, the patients were examined for symptoms of endometritis and abdominal incision site infection. Data analysis was done using SPSS statistical software (version 25) and independent t-tests, Mann-Whitney, Chi-square and Fisher's exact test. P<0.05 was considered significant. Results: Vaginal preparation with chlorhexidine has reduced the incidence of infection in the test group (P<0.05). Although the vaginal preparation with chlorhexidine in the case group decreased the incidence of endometritis compared to the control group, this difference was not significant (P>0.05). Conclusion: The vaginal preparation with chlorhexidine had positive effects in reducing the incidence of infection and endometritis. Therefore, it is recommended to do the vaginal preparation with chlorhexidine in addition to routine abdominal washing to prevent infections after cesarean section.